1997
DOI: 10.1038/bjc.1997.136
|View full text |Cite
|
Sign up to set email alerts
|

Full-term pregnancies and incidence of ovarian cancer of stromal and germ cell origin: a Norwegian prospective study

Abstract: Summary Associations between the incidence of stromal and germ cell ovarian cancer and pregnancies were examined in a follow-up of 1.1 million women aged 20-56 years. Stromal tumours (41 cases) showed no clear associations. Germ cell tumours (71 cases) were related to high-age childbirths and short time since birth.Keywords: stromal tumour; germ cell tumour; parity; population-based study; prospective study (Cramer and Welch, 1983), but few studies have compared the two cancer types. Furthermore, it has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
(13 reference statements)
4
13
0
Order By: Relevance
“…Perinatal factors including motherÕs exposure to exogenous oestrogen during the pregnancy and high pregnancy body weight have been associated with an increased risk. In addition, use of oral contraceptives is associated with an increased risk of germ cell tumours, but the role of parity is unclear (Horn-Ross et al, 1992;Adami et al, 1994;Albrektsen et al, 1997). Our study suggests that young women born in recent decades have experienced a higher risk of developing germ cell ovarian cancer.…”
Section: Cohort Effectmentioning
confidence: 63%
See 2 more Smart Citations
“…Perinatal factors including motherÕs exposure to exogenous oestrogen during the pregnancy and high pregnancy body weight have been associated with an increased risk. In addition, use of oral contraceptives is associated with an increased risk of germ cell tumours, but the role of parity is unclear (Horn-Ross et al, 1992;Adami et al, 1994;Albrektsen et al, 1997). Our study suggests that young women born in recent decades have experienced a higher risk of developing germ cell ovarian cancer.…”
Section: Cohort Effectmentioning
confidence: 63%
“…Previous studies have suggested that epithelial and non-epithelial ovarian tumours have different aetiologies (Horn-Ross et al, 1992;Albrektsen et al, 1997). In addition, the aetiology of mucinous tumours is reported to be different from other epithelial tumours (Risch et al, 1996).…”
Section: Cohort Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This group includes different entities such as stromal, germinal tumours, sarcomas and some others that are unclassifiable [1].…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence of OGCTs at all ages is about 0.5-1 in 100,000. Predisposing risk factors are currently poorly understood [5][6][7]. OGCTs are classified as dysgerminomatous or non-dysgerminomatous.…”
Section: Introductionmentioning
confidence: 99%